Analysis of Modern Muslim Community's Understanding of Pregnancy Myths - Indriani, Irma (Fusshilat : Jurnal Studi Pendidikan dan Keislaman, 2024)
Abstrack : Myth is a form of oral literature broadly encompassed as a result of literary creation, its existence inseparable from the dialectic between author, society, and reader. Myths are stories set in the past, containing interpretations of the universe, and believed to have truly occurred by those who tell them or their followers. A commonly held belief among communities is the myth surrounding pregnant women. Pregnant women are required to adhere to believed practices without understanding the reasons, aims, and essence of the myths they follow. They simply observe taboos, believe, and trust in order to avoid bad luck. They dare not adopt a critical stance by questioning their parents about the meaning and purpose of these myths, as doing so would be deemed disrespectful and confrontational. This article examines the community's perceptions and beliefs regarding myths, covering aspects of cultural traditions, supernatural spiritual beliefs, scientific knowledge, health considerations, and religious aspects. Abstrak : Mitos adalah salah bentuk sastra lisan yang tercakup secara umum sebagai hasil dari kesusastraan, keberadaannya tidaklah lepas dari dialektika antara pengarang, masyarakat, dan pembaca. Mitos berupa kisah berlatar masa lampau, mengandung penafsiran tentang alam semesta, serta dianggap benar-benar terjadi oleh yang punya cerita atau penganutnya. Kepercayaan masyarakat yang masih sering dipercayai oleh masyarakat, yaitu mitos terhadap perempuan yang sedang hamil. Perempuan yang sedang hamil diharuskan melakukan hal-hal yang dipercayai tanpa mengetahui alasan, tujuan, dan hakikat dari mitos yang ia laksanakan. Mereka hanya menjalankan berpantang, meyakini, dan mepercayai agar tidak kualat. Tidak berani bersikap kritis dengan bertanya pada orang tua tentang maksud dan tujuannya melaksanakan mitos tersebut karena apabila bertanya malah akan dianggap tidak hormat dan membantah kepada orang tua. Dalam artikel ini mengkaji tentang persepsi dan keyakinan masyarakat terhadap mitos mulai dari aspek tradisi budaya, keyakinan spiritual supranatural, ilmu pengetahuan, aspek kesehatan dan aspek agama.